Percepção ambiental da relação homem-natureza pelos jovens do/no campo em Paranatama-PE - Barros, Helber Corrêa de (2013)
Man´s relationship with nature every day becomes more complex, with relations what are intensifying and diversifying. These relationships weave reality and, within them, the subjects will be positioned, interacting between themselves. Through perception and others contacts with the environment which we live taking part of and it composing it whiles he will become part of us. The perception is an experience endowed with meaning, having been described in the actual act of sense and meaning. In the context of man-nature relationship that perception turns to the understanding of man as nature and man attending this nature, building relationships in favor of integration or even destruction, and thus may become subject receives its own actions. These relationships, however, are not considered as sums of subjects, prints, objects or actions, because it does not give as something simple. Thus, in order to identify this diversity in its deeper aspects emerged as the relational field goal, investigate the environmental perception of the man-nature relationship by young / field and therefore know the meanings attributed to the significant and underlay of his speech. And for that, took 96 young in the Paranatama field Pernambuco State. Which were subjected to the technique of free association of words, adapted the technique of Abric (1994). Using the theme inductor, the term Human-Nature, five words were remembered, justifying them, followed by the most important evocation and later, justifying it as well. These consisted based on content analysis, the five significant: (I) Environment / Nature / Environment - represented by evocations: water, forest, planet, landscape, environment, nature, ecological context and dependence. (II) Environmental Problems - appointed by evocations: deforestation, pollution and destruction. The signifier (III) Productive Activities - were represented by evocations: farm, farming, land, planting, food, force, work, power, joy, living. (IV) Environmental Protection - was represented by evocations: reforestation, preservation and people. And finally, (V) Environmental Ethics - represented by evocations: respect, love, life, determination, positive, happiness and consciousness. The significant meanings and shows us that pervades a preoccupation with finitude of nature and, therefore, man´s relationship to nature needs to be rethought, redefining the meaning of the word life taking into consideration the nature of the discourse of caring for which ensures survival. This discourse, rooted in the perception of these young man-nature relationship that also signals the need for a systematic work in terms of an epistemological approach to environmental education by giving it meaning, applicability in the formal and informal education.